CBR test on reinforced clay - Chegenizadeh, Amin; Nikraz, Hamid (Canadian Geotechnical Society, 2011)
Geosynthetic fibers are an established family of geomaterials used in a wide variety of civil engineering applications such as pavement systems. In pavement design, CBR ratio count as an important parameter. This study aims to investigate effect of fiber inclusion on CBR ratio. A series of laboratory investigation were carried out to evaluate effects of reinforcing the sub grade soil in pavement system with randomly distributed plastic fibers. In this study, two types of clay and one type of fiber were used. CBR test were conducted on unreinforced samples as well as reinforced ones at different fiber contents (i.e. 0.1%, 0.3%) and different fiber length (i.e. 10mm , 25 mm and 50mm).The results of CBR test showed that the CBR ratio for reinforced clay increased even more than two times in some cases as fiber content and fiber length increased. The results proved that application of short randomly distributed fiber is a good method to apply in practical projects.